2013
DOI: 10.1557/opl.2013.582
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Hydrogen Peroxide as an Oxidant for Atomic Layer Deposition and Related Novel Delivery System

Abstract: Proposed is the use of Hydrogen Peroxide (H2O2) as the ideal oxidant for atomic layer deposition of metal oxide films. H2O2 has similar oxidation properties to Ozone while simultaneously having slightly stronger proton transfer properties than water. Vital to the success of any vapor phase chemistry is delivery of stable compositions, temperature and pressure. This study demonstrates the viability of a new membrane technology for the precise delivery of H2O2/ H2O mixtures starting from a liquid range of 30-70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, ozone must be generated in situ, which involves additional equipment and cost [32]. Hydrogen peroxide (H 2 O 2 ) can be an ideal alternative to ozone or H 2 O, as H 2 O 2 has similar oxidation properties as ozone (oxidation potential of O 3 = 2.1 V versus 1.8 V for H 2 O 2 ) while simultaneously having slightly stronger proton-transfer properties than water (H 2 O 2 pKa = 6.5 versus pKa = 7.0 for water) [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ozone must be generated in situ, which involves additional equipment and cost [32]. Hydrogen peroxide (H 2 O 2 ) can be an ideal alternative to ozone or H 2 O, as H 2 O 2 has similar oxidation properties as ozone (oxidation potential of O 3 = 2.1 V versus 1.8 V for H 2 O 2 ) while simultaneously having slightly stronger proton-transfer properties than water (H 2 O 2 pKa = 6.5 versus pKa = 7.0 for water) [33].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of AlO x TFE layers deposited by AP-SALD using oxygen sources other than H 2 O, especially H 2 O 2 , have yet to be characterized in detail and incorporated into PSC device studies. Only a limited number of previous studies have considered H 2 O 2 as an oxidant for conventional ALD [34,35] and to the best of our knowledge, there are currently no published reports on the effect of using H 2 O 2 in a spatial ALD process, which could be partially due to difficulty in dosing pure H 2 O 2 , since it is often supplied as a mixture with H 2 O, hindering analysis of its chemical reaction mechanisms and process conditions [33].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other commercially available systems, our vaporized hydrogen peroxide system operates at reduced pressure, which causes the feed solution of hydrogen peroxide in water to vaporize and occupy the vessel in the gas phase, based on the principles of Raoult’s law and Dalton’s law of partial pressures [11]. The pressure within a vacuum chamber is reduced, causing a solution of hydrogen peroxide and water to vaporize and occupy the vessel in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional oxidants and oxygen sources in ALD and MLD are ozone, O 2 plasma, and water. It has been demonstrated that, for example, Al 2 O 3 deposited by using TMA + H 2 O 2 is denser and the monolayer growth initiates faster than the films deposited by using H 2 O as an oxygen source. , H 2 O 2 has been used scarcely as an oxidizer for ALD processes, but hardly ever for MLD with organic precursors. , …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that, for example, Al 2 O 3 deposited by using TMA + H 2 O 2 is denser and the monolayer growth initiates faster than the films deposited by using H 2 O as an oxygen source. 15,16 H 2 O 2 has been used scarcely as an oxidizer for ALD processes, but hardly ever for MLD with organic precursors. 17,18 Different molecular modeling techniques can be used to support experimental characterization of thin film structures and 19 The dissociative reaction of mono(alkylamino)silane precursors on a hydroxylated SiO 2 (001) surface has also been investigated at the DFT level using the Vienna ab initio simulation package (VASP) simulations.…”
Section: ■ Introductionmentioning
confidence: 99%